2006
DOI: 10.1093/hmg/ddl118
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide expression analysis detects eight genes with robust alterations specific to bipolar I disorder: relevance to neuronal network perturbation

Abstract: The limited number of genome-wide transcriptome analyses using the postmortem brains of bipolar disorder sufferers has not produced a clear consensus on the molecular pathways affected by the disorder. To expand the knowledge in this area, we examined the expression levels of more than 12 000 genes in Brodmann's Area (BA), 46 (dorsolateral prefrontal cortex) from bipolar I disorder and control samples using Affymetrix GeneChips. This analysis detected 108 differentially expressed genes in bipolar brains. Valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 45 publications
2
78
0
1
Order By: Relevance
“…25,31,32 Together with SLC25A12 upregulation in autism, these findings suggested that SLC25A12 might be deregulated in BP and SZ. We used previously studied samples [23][24][25] to investigate SLC25A12 expression in three neocortical regions: orbitofrontal and mid-frontal gyri (BA11), mid-and inferior-frontal gyri (BA46) and the Wernicke's area of the temporal lobe (BA22). No statistically significant differences were detected by quantitative real time RT-PCR between the BP and SZ samples and controls (Supplementary Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…25,31,32 Together with SLC25A12 upregulation in autism, these findings suggested that SLC25A12 might be deregulated in BP and SZ. We used previously studied samples [23][24][25] to investigate SLC25A12 expression in three neocortical regions: orbitofrontal and mid-frontal gyri (BA11), mid-and inferior-frontal gyri (BA46) and the Wernicke's area of the temporal lobe (BA22). No statistically significant differences were detected by quantitative real time RT-PCR between the BP and SZ samples and controls (Supplementary Tables 4 and 5).…”
Section: Resultsmentioning
confidence: 79%
“…We studied AK2, CASQ1 and NDUFV2, which encode mitochondrial proteins; NDUFV2 has been shown to be deregulated in BP and SZ. 25,32 No significant differences in transcript levels for these three genes in BA46 and cerebellum were found between autistic and control samples (Supplementary Tables 2 and 3). SLC25A12 expression in the human embryonic telencephalon Quantitative in situ hybridization was used to investigate the pattern of SLC25A12 expression during human prenatal development. This approach can be used to detect differences in expression between regions, and gradients of expression in a given structure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…ARNTL is upstream of DBP in the circadian clock intracellular molecular machinery, driving the transcription of DBP [Ripperger and Schibler, 2006;van der Veen et al, 2006]. An increase in ARNTL gene expression was reported in postmortem brains from bipolar subjects [Nakatani et al, 2006]. Seasonal affective disorder (SAD), a variant of bipolar disorder [Magnusson and Partonen, 2005], is tied to the amount of daylight, which is a primary regulator of circadian rhythms and clock gene expression; associations between polymorphisms in the clock genes ARNTL, PER2, and NPAS2 and SAD have previously been reported [Johansson et al, 2003;Partonen et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, gene expression data from post mortem brains of bipolar patients were compared with those of healthy controls in two independent studies (6,7). While post mortem approaches certainly cannot reveal cyclic changes of gene expression, these studies also failed to yield a single overlapping candidate gene for bipolar disease.…”
Section: Introductionmentioning
confidence: 99%